Three new species of the genus Habrobathynella Schminke, 1973 (Syncarida, Parabathynellidae) from the peninsular India - Totakura, Venkateswara Rao; Reddy, Yenumula Ranga (Zootaxa, 2014)
The genus Habrobathynella Schminke, 1973, presently contains 11 species: two species from Madagascar and nine from the peninsular India. Two new species of this genus, viz. H. ajraoi n. sp., and H. parakrishna n. sp., both collected in the phreatic waters of farm bores, and one new species of the same genus, H. pseudoindica n. sp., taken from the hyporheic zone of the River Krishna, are described and illustrated, and their position in the genus is discussed. H. ajraoi n. sp. has a unique combination of characters, viz. male Th VIII penile region extending well beyond basipod; basipodal seta unusually long, overreaching penile region; uropodal sympod with inhomonomous row of seven spines, with penultimate and ultimate spines being longer than proximal ones; mandibular tooth of ventral edge fused, and pars molaris fork-like with only four small, fused teeth; labrum with eight elongate teeth; female Th VIII subovate in outline; and maxilla with three unequal setae on proximal segment. H. parakrishna n. sp. is distinct from its congeners in having only moderately produced male Th VIII penile lobes; antennular sixth segment with three unequal aesthetascs subapically; maxilla with only 1 seta at inner distal corner of proximal segment; uropodal sympod with inhomonomous row of five spines, penultimate spine longest and thickest, and ultimate spine as long as proximal ones; and labrum slightly vaulted, bearing 16 teeth. H. pseudoindica n. sp. has a relatively short, subglobular male Th VIII; uropodal sympod with inhomonomous row of four spines, ultimate one longest; pleotelson slightly protruded in lateral view; maxilla with two rather unequal setae on first segment; labrum vaulted, with ten main, large teeth. Furthermore, the principal morphological characters and their states among the habrobathynellids, with special reference to the new species, are briefly discussed.